Eicosapentaenoic acid in serum phospholipids relates to a less atherogenic lipoprotein profile in subjects with familial hypercholesterolemia - Sala-Vila, Aleix; Cofán, Montserrat; Mateo-Gallego, Rocío; Cenarro, Ana; Civeira, Fernando; Ros, Emilio (The Journal of nutritional biochemistry, 2013)
Familial hypercholesterolemia (FH) carries an increased vascular risk due to lifelong elevation of the number of circulating low-density lipoprotein (LDL) particles, but also to alterations in triglyceride and high-density lipoprotein (HDL) metabolism. Supplementation with eicosapentaenoic (EPA) or docosahexaenoic (DHA) acids reduced LDL particle number and/or increased LDL size in different populations, but studies in FH are scarce. We investigated cross-sectionally whether intake of EPA and DHA in the usual diet is associated with a less atherogenic lipoprotein profile in subjects with FH (n=215). Lipoprotein particle number and size distributions were assessed with nuclear magnetic resonance spectroscopy. EPA and DHA proportions in serum phosphatidylcholine, a biomarker of fish intake, were determined by gas chromatography. After adjusting for cardiovascular risk factors, including fasting triglycerides, serum phosphatidylcholine EPA (but not DHA) related inversely to medium VLDL, total LDL particle number and very small LDL, resulting in a net direct association with LDL size. Additionally, EPA was directly associated with concentrations of large HDL. We conclude that increased serum phosphatidylcholine EPA derived from seafood intake with the usual diet is associated with a less atherogenic lipoprotein profile in subjects with FH. Increased fish intake and/or EPA supplements might contribute to reduce the residual risk of statin-treated FH subjects.